OP0149 An mri guided treat-to-target strategy in rheumatoid arthritis patients in clinical remission improved mri inflammation but not damage progression – results from the imagine-ra randomised controlled trial. (12th June 2018) - Møller-Bisgaard, S.; Hørslev-Pedersen, K.; Ejbjerg, B.; Glinatsi, D.; Hetland, M.; Ørnbjerg, L.; Møller, J.; Boesen, M.; Christensen, R.; Stengaard-Pedersen, K.; Madsen, O.R.; Jensen, B.; et al.
Abstract : Background: Magnetic Resonance Imaging (MRI) bone marrow oedema (BME)/osteitis and MRI synovitis have been identified as predictors of structural damage progression in rheumatoid arthritis RA. 1 2 Targeting MRI remission may reduce inflammation and halt damage progression. Objectives: To investigate whether a 2 year treat-to-target (T2T) strategy targeting MRI remission (defined as absence of BME) suppresses MRI-determined measures of disease activity and structural joint damage in RA patients in clinical remission. Methods: In the two year investigator initiated, randomised, open label multicentre IMAGINE-RA study, 200 RA patients in clinical remission (defined as DAS28-CRP<3.2 and no swollen joints) receiving conventional synthetic disease-modifying antirheumatic drugs (csDMARDSs) were randomised 1:1 to a conventional DAS28-CRP guided T2T treatment strategy targeting DAS28 <3.2 and no swollen joints or an MRI guided T2T treatment strategy applying the same clinical T2T strategy and in addition targeting absence of MRI BME. Patients were followed every 4 months over a 2 year follow-up period. In all patients contrast-enhanced MRIs of the 2nd–5th metacarpophalangeal (MCP) joints and wrist of the dominant hand were performed at baseline, 12 and 24 months. In the MRI T2T arm MRI was performed every 4 months ahead of the clinical visit and assessed for presence/absence of BME by one blinded evaluator so the result was available for the investigator at the visit. In the conventional T2T arm MRI findings were blinded to the investigator. If treatment target was not met treatment was escalated according to a predefined treatment algorithm starting with increment in csDMARD and then adding biologic DMARDs. MRIs (0, 12 and 24 months) were evaluated according to the RAMRIS scoring system, with known chronology by one blinded experienced reader. Pearson's chi-square statistics and repeated-measures logistic regression models were used to assess outcomes. Results: MRI outcomes of inflammation and damage at 24 months are presented in the table 1. The MRI T2T arm showed statistically significant reductions at 24 months in all inflammatory endpoints (osteitis, tenosynovitis and total inflammation score, p<0.018), except synovitis, (p=0.074), compared to the conventional T2T arm. No differences between treatment strategies were seen in damage progression. Conclusions: An MRI T2T strategy, aiming to eliminate MRI BME, was more effective than a conventional T2T strategy in reducing MRI inflammation but not MRI damage progression. The reduced inflammatory load caused by the MRI T2T strategy may reduce long-term structural joint damage and improve patient-reported outcomes, but more than two years follow-up data are needed to clarify this. Clinicaltrials.gov Identifier: NCT01656278 Reference: [1] Hetland, et al. Ann Rheum Dis2009;68(3). [2] Boyesen, et al. Ann Rheum Dis2011;70(3). Disclosure of Interest: None declared